2014
DOI: 10.2310/7290.2014.00011
|View full text |Cite
|
Sign up to set email alerts
|

111 In-Trastuzumab Scintigraphy in HER2-Positive Metastatic Breast Cancer Patients Remains Feasible during Trastuzumab Treatment

Abstract: Human epidermal growth factor receptor (HER)2 imaging with radiolabeled trastuzumab might support HER2-targeted therapy. It is, however, frequently questioned whether HER2 imaging is also possible during trastuzumab treatment as the receptor might be saturated. We studied the effect of trastuzumab treatment on 111In-trastuzumab uptake. Patients received trastuzumab weekly and paclitaxel once every 3 weeks. 111In-trastuzumab was injected on day 1 of cycle 1 and day 15 of cycle 4. Whole-body planar scintigraphy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 17 publications
(24 reference statements)
3
41
0
1
Order By: Relevance
“…For imaging of a number of antibodies without dose-dependent PK, such as bevacizumab, fresolizumab or the mesothelin-targeting antibody MMOT0530A, a dose of 5 or 10 mg unlabeled antibody was already sufficient for optimal PET imaging (24,29,32,42). However, for HER2 imaging with 89 Zr-trastuzumab, an antibody with clear dose-dependent PK, an additional dose of 50 mg unlabeled trastuzumab is needed for optimal imaging (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…For imaging of a number of antibodies without dose-dependent PK, such as bevacizumab, fresolizumab or the mesothelin-targeting antibody MMOT0530A, a dose of 5 or 10 mg unlabeled antibody was already sufficient for optimal PET imaging (24,29,32,42). However, for HER2 imaging with 89 Zr-trastuzumab, an antibody with clear dose-dependent PK, an additional dose of 50 mg unlabeled trastuzumab is needed for optimal imaging (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…One such approach is the use of trastuzumab labeled with 111 In (half-time, 2.8 d) (9) or 89 Zr (3.3 d) (10) for use with SPECT and PET, respectively, but the slow kinetics of antibodies require imaging several days after administration. One promising method of fast, safe, and accurate imaging that specifically binds to a site on the receptor not occupied by current targeting therapeutic drugs (11)(12)(13) is to use the Affibody (Affibody AB) molecule ABY-025.…”
mentioning
confidence: 99%
“…These data showed that molecular antibody imaging can help identify tumor lesions that are missed by conventional imaging techniques. Second, serial SPECT imaging with 111 In-trastuzumab before and after 12 wk of trastuzumab treatment showed persistent uptake in all tumor lesions, with only a 20% decrease in tumor tracer uptake (17). These data indicated that HER2 is constantly available at the tumor cell surface to bind to trastuzumab and that the tumor is not completely saturated by trastuzumab treatment.…”
Section: Use Of Theranostics In Clinical Decision Makingmentioning
confidence: 72%